Oblivion: A Memoir - HÃ©ctor JoaquÃn Abad Faciolince (Old Street Publishing, 2010)
'Oblivion' is a memorial to the author's father, Hector Abad Gomez, whose criticism of the Colombian regime led to his murder by paramilitaries in 1987."